THE EFFECT OF JICAMA (Pachyrhizus erosus) CONCENTRATION ON THE GROWTH OF Staphylococcus aureus BACTERIA IN SOLID MEDIA - Mirawati, Mega; Prasetyorini, Tri; Irmadhani, Fania (Meditory : The Journal of Medical Laboratory, 2023)
Background:Synthetic media for microbial growth are expensive, thus opening the way for making bacterial growth media using local raw materials at low prices. Jicama is one of the local raw materials that can be used as natural media for the growth of microorganisms. It contains a source of carbohydrates needed for the development of microorganisms. Aims: This study aims to determine the effect of variations in the concentration of Jicama, which has the potential to grow Staphylococcus aureus bacteria. Methods: This study used experimental research with the Static Group Comparison method. In this study, the experimental group Staphylococcus aureus was instilled in Jicama solid media with various concentrations (2%, 3%, 4%, 5%, 6%) with five repetitions. The results: The results showed that the average number of Staphylococcus aureus bacteria colonies in jicama flour with a concentration of 2% was 0, a concentration of 3% was 0, a concentration of 4% was 0.8, a concentration of 5% was 1.4, and at a concentration of 6% was 2.2. The results of the Kruskal-Wallis test with a degree of confidence of 0.05 obtained a p-value = 0.000 where the p-value 0.05 so that it can be concluded that there is a significant effect of variations in the concentration of jicama flour on the growth of Staphylococcus aureus bacteria. Conclusions:For future researchers, it is necessary to conduct further research using higher concentrations of jicama flour and by adding other nutrients, such as animal protein, so that the growth of Staphylococcus aureus bacteria is more optimal.